A randomised trial on platelet function-guided de-escalation of antiplatelet treatment in ACS patients undergoing PCI - Sibbing, Dirk; Aradi, Dániel; Jacobshagen, Claudius; Gross, Lisa; Trenk, Dietmar; Geisler, Tobias; Orban, Martin; Gori, Tommaso; Hadamitzky, Martin; Merkely, Béla; Kiss, Róbert Gábor; Komócsi, András; Dézsi, Csaba A.; Thalmeier, Andreas; Löw, Anja; Holdt, Lesca; Teupser, Daniel; Ince, Hüseyin; Felix, Stephan B.; Parma, Radoslaw; Malek, Lukasz; Horstkotte, Jan; Baylacher, Monika; Schwinger, Robert; Rieber, Johannes; Mudra, Harald; Hausleiter, Jörg; Huber, Kurt; Neumann, Franz-Josef; Koltowski, Lukasz; Huczek, Zenon; Mehilli, Julinda; Massberg, Steffen; on behalf of the TROPICAL-ACS Investigators (Thrombosis and Haemostasis, 2017)
Outcomes of acute coronary syndrome (ACS) patients undergoing percutaneous coronary intervention (PCI) have been significantly improved with the use of potent P2Y12 receptor inhibitors like prasugrel. While most of the ischaemic risk reduction for prasugrel versus clopidogrel was demonstrated in the early treatment period, the risk of bleeding became particularly prominent during the chronic course of therapy. It may therefore be a valid approach to substitute prasugrel for clopidogrel in the early phase of chronic antiplatelet treatment after PCI. In the Testing Responsiveness To Platelet Inhibition On Chronic Antiplatelet Treatment For Acute Coronary Syndromes (TROPICAL-ACS) trial, we aim to compare standard prasugrel therapy with a de-escalating antiplatelet treatment approach guided by platelet function testing (PFT). The study is an investigator-initiated European multicentre, randomised clinical trial in biomarker-positive ACS patients after successful PCI. Two thousand six hundred patients will be randomised prior to hospital discharge in a 1:1 fashion to either receive standard prasugrel therapy (control group) or de-escalating therapy (one-week prasugrel followed by one-week clopidogrel and PFT-guided maintenance therapy from day 14 after hospital discharge, monitoring group). Patients of the monitoring group with high on-clopidogrel platelet reactivity (HPR) based on Multiplate analyzer testing (HPR: ≥ 46U per consensus definition) will be switched back to prasugrel, whereas those without HPR (<46 U) will continue clopidogrel treatment. The overall study treatment duration will be one year in both groups. The primary endpoint of the study is net clinical benefit (combined incidence of cardiovascular death, myocardial infarction, stroke and bleeding ≥ grade 2 according to BARC criteria) one-year after randomisation. TROPICAL-ACS is the first large-scale, randomised controlled trial assessing the clinical value of a PFT-guided de-escalation of antiplatelet treatment in biomarker positive ACS patients undergoing PCI.ClinicalTrials.gov Identifier: NCT01959451
Keywords: Acute coronary syndrome; platelets; antiplatelet drugs